Silvopastoralism and Sustainable Land Management. Proceedings of an International Congress on Silvopastoralism and Sustainable 2005
DOI: 10.1079/9781845930011.0275
|View full text |Cite
|
Sign up to set email alerts
|

Some ecological impacts of Quercus rotundifolia trees on the understorey environment in the "montado" agrosilvopastoral system, southern Portugal.

Abstract: The influence of Quercus rotundifolia trees on precipitation chemistry, soil physical and chemical characteristics, light, nutrient and water availability and biomass production of the understorey was studied in a "montado" at Évora (southern Portugal). Ca and K were added to the soil by throughfall (21.05 and 38.49 kg/ha, respectively) and gross rainfall (3.49 and 3.98 kg/ha). Thickness of the soil organic layer and nutrient availability decreased with the distance from the tree trunk and were higher in ungra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…In our study, water interception and transpiration should overweigh the positive effects of trees on water-holding capacity, as observed in North American savannas [27]. A similar pattern has been reported by Nunes et al [30], for Portuguese dehesas with an annual rainfall of 666 mm. In more humid dehesas (annual rainfall above 700 mm) soil water content was always higher beneath than beyond the tree canopy [20].…”
Section: Effect Of Trees On Soil Water Content Distributionsupporting
confidence: 69%
“…In our study, water interception and transpiration should overweigh the positive effects of trees on water-holding capacity, as observed in North American savannas [27]. A similar pattern has been reported by Nunes et al [30], for Portuguese dehesas with an annual rainfall of 666 mm. In more humid dehesas (annual rainfall above 700 mm) soil water content was always higher beneath than beyond the tree canopy [20].…”
Section: Effect Of Trees On Soil Water Content Distributionsupporting
confidence: 69%
“…The study shrubs may have a positive role on SOC (10.3-11.4 g kg −1 in the 0-5 cm top soil layer), as reported for other Mediterranean shrubs (Moro et al 1996;Monokrousos et al 2004) and shrubs in a subtropical savanna (Hibbard et al 2001), following the pattern observed for trees in oak woodlands of Mediterranean areas (Dahlgren et al 1997;Nunes 2004;Moreno and Obrador 2007). However, relative to barren areas (8.1 g kg −1 ), the increment of SOC was low, which is in line with average values reported by Moreno and Obrador (2007) for dehesas encroached after 10-15 years.…”
Section: Soil Propertiesmentioning
confidence: 54%
“…Those values are within the range reported by Escudero et al (1985) for litter amount beneath Q. rotundifolia (1.7-4.6 Mg DM ha −1 ). Also, amounts of necromass under shrub canopies fall within the range observed by Nunes (2004) for Q. rotundifolia (1.3-3.0 Mg DM ha −1 ), in the neighbourhood of the study area. Similar necromass observed for CL and Q. rotundifolia is in agreement with litterfall amounts of the same magnitude, and also with the similar decomposition rate exhibited by the leaf litter of CL (−0.44 year −1 ) as compared to that for Q. rotundifolia (−0.48 year −1 ) (Sá et al 2005).…”
Section: Annual Potential Return Of Bio-elementsmentioning
confidence: 69%
See 2 more Smart Citations